2019
DOI: 10.1002/aur.2078
|View full text |Cite
|
Sign up to set email alerts
|

Association between CNTNAP2 polymorphisms and autism: A family‐based study in the chinese han population and a meta‐analysis combined with GWAS data of psychiatric genomics consortium

Abstract: Autism is a childhood neuropsychiatric disorder with evidence of a strong genetic component in the complex etiologies. Contactin‐associated protein‐like 2 (CNTNAP2), a member of the neurexin superfamily, plays an essential role in neural development. CNTNAP2 was considered as one of the most susceptible genes for autism spectrum disorder (ASD). Some studies indicated the association of CNTNAP2 with ASD, while others reported no association. Given the inconsistent results of the previous studies, we performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…According to the AutDB database (http://autism.mindspec.org/autdb/Welcome.do, updated January 2020), 3145 animal models of ASD, including inbred, induced and genetic mouse models, are currently available. Genetic studies demonstrated that mutations in several genes coding for synaptic proteins, such as SHANK3 [2], NLGN3, NLGN4X [3], CNTNAP2 [4] and GABRB3 [5], are associated with ASD. Furthermore, ASD is syndromic with other neuropsychiatric conditions with single gene mutations including Fragile X syndrome (FMR1) [6], tuberous sclerosis (either TSC1 or TSC2) [7], Cowden syndrome (PTEN) [8] and Angelman syndrome (UBE3A) [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the AutDB database (http://autism.mindspec.org/autdb/Welcome.do, updated January 2020), 3145 animal models of ASD, including inbred, induced and genetic mouse models, are currently available. Genetic studies demonstrated that mutations in several genes coding for synaptic proteins, such as SHANK3 [2], NLGN3, NLGN4X [3], CNTNAP2 [4] and GABRB3 [5], are associated with ASD. Furthermore, ASD is syndromic with other neuropsychiatric conditions with single gene mutations including Fragile X syndrome (FMR1) [6], tuberous sclerosis (either TSC1 or TSC2) [7], Cowden syndrome (PTEN) [8] and Angelman syndrome (UBE3A) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the remaining six articles, two were already in our dataset from the literature search from PubMed. Finally, four articles from the GWAS catalog were manually added to 27 articles previously screened from PubMed, leading to a total of 31 eligible articles [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] being included in the systematic review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in the same Chinese Han population showed a significant correlation between ASD and haplotype T-A (rs7794745-rs10500171, P = 0.011) or haplotype A-T-A (rs10244837-rs7794745-rs10500171) of the CNTNAP2 gene [ 34 ]. However, several other studies reported no significant association between rs7794745 and the risk of ASD [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice lacking Cntnap2 display striking similarity to the core deficits in behavioral and cognitive functions observed in patients with ASD [ 14 ]. The intronic SNP rs7794745 in the CNTNAP2 gene was reported to be a risk factor for ASD in some studies [ 15 17 ], but not others [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%